Behavioral control with anti-littering behavioral intention at Iran Forest Park - Aziz, Azlizam; Talooki, Kambiz Yousefi; Jamaludin, Mazlina (Exeliq Publishing, 2018)
Littering is the prevalent problem among Iranian forest parks. Forest parks’ managers made several efforts to overcome this undesirable problem. Unfortunately, the effectiveness of their approaches was restricted to short-term and to specific forest park, only because of neglecting a large number of underlying factors and beliefs. This study was conducted to determine the relationship among two variables, which are attitude, perceived behavioral control with intention of forest parks’ visitors to perform anti-littering behavior through utilizing theory of planned behavior. Simple random sampling and convenience sampling were used in the survey. The sample of this study consisted of 160 forest park millennial visitors who come to the Shahid Zare Forest Park, Iran during peak season period in the year of 2017. Inferential statistics were utilized to analyze the data collected using Smart PLS 3.0. The study results revealed the perceived behavioral control (β= 0.735) is more effective variable than active anti littering behavior. Based on the finding of this study, it could be useful for forest park’s managers to consider perceived behavioral control more in their management approaches to ensure cleanliness in the forest parks to obtain long term behavioral change amongst forest park visitors.